Exploring distraction techniques and parental satisfaction during infant immunization: a pilot study in aspirational district Darrang and non-aspirational districts Karimganj of Assam - Sharma, Deepanshu; Sharma, Rahul; Sharma, Jyoti; Jha, Punit (International Journal Of Community Medicine And Public Health, 2024)
Background: In India, the percentage of children aged 12-23 months who have had full immunization coverage (FIC) has increased dramatically from 62% to 76%. UNICEF, 2022. As stated in the WHO report for 2022. Global coverage decreased to 81% in 2021 from 86% in 2019. Methods: The study’s methodology involved studying how the 4 S’s technique, oral sucrose, and each of them affect parents’ satisfaction and infants’ perception of pain after vaccination in Darrang aspirational and Karimganj non-aspirational districts. Eighty infants were involved in the pilot project, split into four groups of ten infants each. Results: In the study at Civil Hospital Mangaldoi, group C reported the highest parental satisfaction (mean=3.2) with no dissatisfaction and the lowest mean pain intensity (1.3, SD=0.48). Group A had 100% satisfaction (mean=3.1, SD=0.31), group B had 90% satisfaction (mean=3.0, SD=0.47), and the control group had the lowest satisfaction (30%, mean=2.3, SD=0.67) with 70% dissatisfaction. Group C’s outcomes demonstrate both the highest satisfaction and the least intense, most consistent pain perception among participants. Conclusions: This study’s conclusion emphasizes how critical it is to overcome vaccine reluctance and enhance immunization experiences by employing efficient pain control strategies. The findings support the implementation of interventions such as sucrose administration and other pharmacological and non-pharmacological approaches to reduce pain associated with vaccinations, particularly in paediatric populations.